Mathematics anxiety and mathematical calculation in deaf children: A moderated mediation model of mathematics self-efficacy and intelligence. (January 2022) - Chen, Lilan; Wang, Yan
Highlights: Explore the difference between hearing children and deaf children in the relationship between mathematics anxiety, mathematics self-efficacy, intelligence, and mathematical calculation. Explore the inner mechanisms between mathematics anxiety and mathematical calculation in deaf children. Using the SPSS macro PROCESS Model 4 and 7 to conduct a simple mediation analyses and moderated mediation analyses and find out the indirect effect between mathematics anxiety and mathematical calculation via mathematics self-efficacy is moderated by intelligence in deaf children but not in hearing children. Sheds light on the similar studies on the relationship between emotional factors and mathematics achievement in deaf children. Abstract: Background: Previous studies have shown the relationship between mathematics anxiety and math performance in deaf students, but their inner influencing mechanism remains unclear. Aim: To examine a moderated mediation model between mathematics anxiety and mathematical calculation, with intelligence as a moderator, and mathematics self-efficacy as a mediator. Methods: A sample of 247 deaf children from 2 special education schools and 247 hearing children (matched in intelligence) from one mainstream school in China completed computerized tests of intelligence and mathematical calculation and self-report questionnaires of mathematics anxiety and mathematics self-efficacy. Simple mediation analyses and moderated mediation analyses were conducted using PROCESS, and a simple slopes method was employed to plot the conditional indirect effects. Results: There was a significant negative correlation between mathematics anxiety and mathematical calculation, and between mathematics anxiety and mathematics self-efficacy in deaf children and hearing children. However, mathematics self-efficacy was positively associated with mathematical calculation in deaf children but not in hearing children, and the significantly negative relationship between mathematics anxiety and intelligence was observed only in deaf children but not in hearing children. Mathematics self-efficacy partially mediated the association between mathematics anxiety and mathematical calculation in deaf children; and the indirect effect between mathematics anxiety and mathematical calculation via mathematics self-efficacy was moderated by intelligence in deaf children but not in hearing children. Conclusions: The results were discussed to illuminate the mechanism in relation to the practical implication for the intervention and early development of mathematics performance in deaf children.